2022
DOI: 10.18795/gumusmaviatlas.1119236
|View full text |Cite
|
Sign up to set email alerts
|

Covid 19 Pandemi Sürecinde Okul Öncesi Öğretmen Adaylarının Özyeterlikleri ve Gelecek Kaygıları Arasındaki İlişkinin İncelenmesi

Abstract: Araştırma okul öncesi öğretmen adaylarının özyeterlilik inançları ile gelecek kaygıları arasındaki ilişkinin incelenmesi amacıyla planlanmıştır. Araştırmanın çalışma grubunu Mehmet Akif Ersoy Üniversitesi Okul Öncesi Öğretmenliği bölümünde öğrenim gören ve araştırmaya gönüllü olarak katılmayı kabul eden toplam 316 öğrenci oluşturmuştur. Araştırmaya alınan öğretmen adaylarının %76.9’unun kadın, %23.1’inin erkek olduğu, çoğunluğunun bölümü isteyerek seçtiği (%95.6) ve mesleğe kendini hazır hissettiği (%70.3) yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…It was determined that female preschool teacher candidates' emotion regulation hiding sub-dimension and occupational anxiety were significantly higher than male teacher candidates. In the studies in the literature, it was concluded that female teacher candidates got higher scores in both emotion regulation skills and occupational anxiety (Akgün et al, 2007;Arslan et al, 2023;Dalgar & Kaytez, 2022;Eskici, 2016;Güngör & Gül, 2021;Koçin, 2022;Saban et al, 2004;Tabancalı, Çelik, & Kormaz, 2016). The fact that female teacher candidates have higher social relations may have positively reflected their emotion regulation skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was determined that female preschool teacher candidates' emotion regulation hiding sub-dimension and occupational anxiety were significantly higher than male teacher candidates. In the studies in the literature, it was concluded that female teacher candidates got higher scores in both emotion regulation skills and occupational anxiety (Akgün et al, 2007;Arslan et al, 2023;Dalgar & Kaytez, 2022;Eskici, 2016;Güngör & Gül, 2021;Koçin, 2022;Saban et al, 2004;Tabancalı, Çelik, & Kormaz, 2016). The fact that female teacher candidates have higher social relations may have positively reflected their emotion regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Gülbahçe et al (2012) and Gündoğdu et al (2008) discovered that pre-service teacher candidates had a high level of anxiety about KPSS. On the other hand, Dalgar and Kaytez (2022) discovered that pre-service teacher candidates who don't feel prepared to teach have higher levels of anxiety that are task-, student-, and self-focused. It can be understood that teacher candidates' increased anxiety during the exam preparation process is due to their uncertain future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations